Performative Parametric Design of Radiation Responsive Screens - Marroquin, Henry; Thitisawat, Mate; Vermisso, Emmanouil (ARCC Conference Repository, 2014)
In subtropical or tropical region, shading is one of the most important design strategies due to exposure to intense solar radiation. The study addresses the need for flexible design method identified intoday's architectural practice. Different workflows for coupling the parametric design with simulations of heatflow and radiation are examined. A workflow consists of tools running on modeling or simulation platform. The paper establishes three workflows, static, cross-platform and dynamic. Each workflow has similar capabilities in terms of access to simulation engines but different flow of information. Therefore, they can beemployed in different design circumstances. The current investigation indicates the need for multi-objectiveoptimization in the future.